Ecological insights post-restoration from two decades of mangrove forest succession in Pangpang Bay, East Java, Indonesia - HARI SULISTIYOWATI; RENDY SETIAWAN; ARIF MOHAMMAD SIDDIQ; RETNO WIMBANINGRUM; MUHAMMAD AFRIYANTO; ELA APRILIYANTI HASANAH; BUDI PUTRA MULYADI; ABDILLAH BARAAS (Society for Indonesian Biodiversity, 2025)
Abstract. Sulistiyowati H, Setiawan R, Siddiq AM, Wimbaningrum R, Afriyanto M, Hasanah EA, Mulyadi BP, Baraas A. 2025. Ecological insights post-restoration from two decades of mangrove forest succession in Pangpang Bay, East Java, Indonesia. Biodiversitas 26: 2299-2308. The Mangrove Pangpang Bay (MPB) in Banyuwangi District, East Java, Indonesia, has suffered significant degradation from anthropogenic pressures. A restoration project was launched in the late 1990s, and between 2000 and 2003, approximately 300,000 trees were planted across 70 ha. However, 22 years later, little is known about the structural and functional dynamics of the mangrove forest's succession. This study assesses the structural complexity, ecological functionality, and environmental resilience of the restored mangrove forest in MPB. Tree vegetation data were collected using 10x10 m² plots, and functional data were obtained through a semi-destructive method. Secondary data on species conservation status and geographic distribution were sourced from the IUCN Red List, while abiotic factors, including temperature, pH, and salinity, characterized environmental conditions. The MPB comprises 11 mangrove species from 5 families and 7 genera, dominated by Rhizophora mucronata and Sonneratia alba. Abiotic conditions, salinity (31.85%), soil pH (7.96), and temperature (29.89?) are favorable for mangrove growth, particularly for the Rhizophora. The Shannon-Wiener Diversity Index (H') was low (0.98), indicating secondary succession influenced by human-led planting. Mangrove tree density averaged 3,719 trees/ha, with 1,392 seedlings/ha, and vegetation volume was 18,556.10 m3/ha. The estimated carbon stock was 104.58 Mg C/ha, equating to 383.49 Mg CO2/ha and 277.42 Mg O2/ha. Salinity correlated positively with carbon stock and tree volume, while pH, temperature, and diversity showed negative correlations, indicating potential trade-offs in shaping the restored ecosystem of MPB. Additionally, the total biodiversity value of MPB was calculated to be 9,733,952,191.99 IDR per hectare.